LEARNING STYLES OF EFL STUDENTS IN ONLINE AND TRADITIONAL LEARNING ENVIRONMENTS - Hikmatova , Nilufar Hamidullayevna; Amriyeva , Shahlo Ozodovna; Burkhanova, Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
This article is devoted to the role and importance of learning styles of English as a foreign language students in both online and distance learning environments